PREVALENCE OF SPONDYLOLISTHESIS IN PATIENTS OF CHRONIC LOW BACK PAIN - AMRITA PAREEK; VAISHALY KISHORE BHARAMBE; SHAINA AGGARWAL; KAPIL PAREEK; DIVYA GAKHAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study is to assess the prevalence of spondylolisthesis in patients with chronic low back pain (CLBP). Methods: This was a cross-sectional and observational study, conducted on patients of CLBP presented and evaluated with relevant radiological investigation in neurosurgery clinics in Rajasthan. Results: The mean age of the study population was 46.62 years with female dominance (73.85%). 63.96% had moderate work followed by severe work 28.98%. The prevalence of spondylolisthesis was 16.61% (47). Conclusion: The present study’s prevalence of lumbar spondylolisthesis was more prone in middle-aged females.